Children with Heiner Syndrome: A Single-Center Experience - Ji Young Lee; Mireu Park; Jae Hwa Jung; Soo Yeon Kim; Yoon Hee Kim; Seung Min Hahn; Seung Kim; Mi-Jung Lee; Hyo Sup Shim; Myung Hyun Sohn; Kyung Won Kim; Min Jung Kim (MDPI AG, 2021)
Heiner syndrome is a rare cause of pulmonary hemosiderosis in children that is triggered by cow's milk allergy. Herein, we describe our experience with three recent cases of Heiner syndrome with diverse clinical courses. We recommend that clinicians should consider the possibility of Heiner syndrome in children who exhibit characteristics of idiopathic pulmonary hemosiderosis.